Tobacco-free School Training Program for Teachers and Tobacco-use among Adolescent Students in the Rural Indian Context: A Quasi-experimental Study - Chatterjee, Nilesh; Kadam, Rajashree; Patil, Deepak; Pillai, Kalpana (Asian Pacific Journal of Cancer Care, 2025)
Introduction: The Indian government has implemented laws banning tobacco sales and advertising to children and adolescents and also mandated guidelines for a tobacco-free school (TFS) to create tobacco-free environments. This study investigated the impact of creating tobacco-free schools on actual tobacco use by students. Methods: The study, using a post-only quasi-experimental design, was conducted in four rural districts of Maharashtra state in western India. Teachers in two intervention districts received annual TFS training for five years, while two comparison districts did not. A cross-sectional survey was conducted in 41 schools, at the end of the five-year period, with 536 students in intervention districts and 516 in comparison districts. Results: Intervention schools reported lesser tobacco use with 14.7% of students self-reporting tobacco use versus 24.2% of students in comparison schools. Logistic regression analysis revealed that lower exposure to TFS, greater peer pressure, and presence of adults using-tobacco at home predicted adolescent tobacco use (p<.001). Conclusion: Creating a tobacco-free school environment seems to positively impact student tobacco-use behavior. However, combining TFS with assertiveness, refusal, and life-skills training to resist peer pressure and involvement of families will be required for successful tobacco-use prevention.